Pengaruh Kualitas Pelayanan dan Cita Rasa Terhadap Minat Beli Ulang Pelanggan (Studi Kasus Pada Nongkaski Coffee and eatery) - Rizal Agfrans Pratama; Ustadus Sholihin; Taufik Akbar (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
Coffee shops that use marketing strategies to achieve customer repurchase intention by providing quality service and good taste, namely Nongkasky Coffee and Eatery. The taste of Nongkasky Coffee and Eatery is quite good, including in the processing and selection of ingredients and has a kitchen expert who knows his field. In addition, it also provides friendly service quality, but waiters are less responsive in handling consumer complaints. This research is a quantitative research. The research location is located at Nongkasky Coffee and Eatery, Kec. Wates Kab. Kediri. The population in this study was 900 consumers. The sample in this study were 60 consumers using the Malhotra sampling technique. The analysis technique used is validity and reliability test, classic assumption test, multiple linear analysis test and hypothesis test. Partially the variable of service quality (X1) has a significant effect on the variable of interest in repeating (Y). Partially taste (X2) has a significant effect on repurchase intention (Y). Simultaneously service quality (X1) and service quality (X2) affect customer repurchase intention (Y).